2016
DOI: 10.1007/s00467-016-3439-9
|View full text |Cite
|
Sign up to set email alerts
|

Preterm neonatal urinary renal developmental and acute kidney injury metabolomic profiling: an exploratory study

Abstract: Introduction AKI staging has been developed in the adult and pediatric populations, but these do not yet exist for the neonatal population. Metabolomics was utilized to uncover biomarkers of normal and AKI associated renal function in preterm infants. The study was comprised of 20 preterm infants with an AKI diagnosis who were matched by gestational age and gender to 20 infants without an AKI diagnosis. Methods Urine samples from pre-term newborn infants collected on day 2 of life were analyzed using broad s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
2
7
0
1
Order By: Relevance
“…For example, Beger et al identified homovanillinic acid sulfate, a dopamine metabolite as the most important marker in the urine of children who developed AKI after cardiac surgery [21]. This finding was confirmed by Mercier et al investigating the urine of neonates with AKI [29]. By contrast, aromatic compounds other than 3-indoxylsulfate and hippurate are not among the important metabolites in our study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For example, Beger et al identified homovanillinic acid sulfate, a dopamine metabolite as the most important marker in the urine of children who developed AKI after cardiac surgery [21]. This finding was confirmed by Mercier et al investigating the urine of neonates with AKI [29]. By contrast, aromatic compounds other than 3-indoxylsulfate and hippurate are not among the important metabolites in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Previous human AKI studies resulted in the identification of a variety of potential metabolite biomarkers [14,24]. Interestingly, almost no overlap exists between the respective metabolites [28][29][30][31][32][33][34] and the metabolites identified in our study. For example, Beger et al identified homovanillinic acid sulfate, a dopamine metabolite as the most important marker in the urine of children who developed AKI after cardiac surgery [21].…”
Section: Discussionmentioning
confidence: 46%
“…BA has been often reported as one of the most common early and late causes of renal function decline in neonates (30). In this study, we also found that asphyxia was significantly associated with an increased risk of impaired renal function in preterm neonates within the first day after birth.…”
Section: Discussionsupporting
confidence: 72%
“…Interindividual differences in levels of metabolites that are substrates for cisplatin transporters may help identify individualized risk of cisplatin AKI. [46][47][48][49][50] Proximal tubule mitochondria are a primary target of cisplatin nephrotoxicity and cisplatin has been shown to alter metabolites associated with oxidant stress (eg, glutathione) and mitochondrial dysfunction (eg, fatty acids) in response to injury. 51,52 Metabolites associated with oxidant stress or mitochondrial dysfunction may be metabolic markers of early nephrotoxicity.…”
Section: Rationalementioning
confidence: 99%